Mapping QTLs and gene validation studies for Mg2+ uptake and translocation using a MAGIC population in rice - Zhi, Shuai; Zou, Wenli; Li, Jinyan; Meng, Lijun; Liu, Jindong; Chen, Jingguang; Ye, Guoyou (Frontiers Media, 2023)
Magnesium (Mg) is an essential element for plant growth and development. Rice is an important food crop in the world, but there are few studies on the uptake and translocation of Mg2+ in rice. We used a multi-parent advanced generation inter-cross (MAGIC) population constructed using four parental lines and genotyped by a 55 K rice SNP array for association analysis to locate QTLs related to Mg2+ uptake and translocation in rice at the seedling stage. Four QTLs (qRMg1, qRMg2, qRMg7 and qRMg8) were detected for the root Mg2+ concentration, which explained 11.45-13.08% of the phenotypic variation. The Mg2+ transporter gene, OsMGT1, was within the region of qRMg1. Three QTLs (qSMg3, qSMg7 and qSMg10) were detected for the shoot Mg2+ concentration, which explained 4.30-5.46% of the phenotypic variation. Two QTLs (qTrMg3 and qTrMg8) were found to affect the translocation of Mg2+ from the roots to the shoots, and explained 10.91% and 9.63% of phenotypic variation. qSMg3 and qTrMg3 might be the same, since they are very close to each other on chromosome 3. Analysis of candidate genes in the region of qSMg3 and qTrMg3 through qRT-PCR, complementation assay in the yeast Mg2+ transport-defective mutant CM66, and sequence analysis of the parental lines suggested that LOC_Os03g04360 may play important roles in Mg2+ uptake, translocation and accumulation in rice. Overexpression of LOC_Os03g04360 can significantly increase the Mg2+ concentration in rice seedlings, especially under the condition of low Mg2+ supply.